Los ingenieros militares y la articulación del Caribe: Agentes locales para una historia global. - Gámez Casado, Manuel (Latin American Research Review, 2026)
The article analyzes the work of military engineers as local agents for the resolution of global conflicts that affected the Spanish Caribbean during the eighteenth century. In addition, it examines the engineers’ integration into the knowledge transfer circuits that formed around the main Caribbean cities of the Spanish Empire, as they participated in a transfer of culture that materialized in ideas, institutions, and instruments. The analysis of these transfers allows us to understand the adaptation of technical knowledge promoted by engineers in their architecture, which would be decisive in the constitution of a certain image of imperial power on the other side of the Atlantic.